Relationship between emotional motivation and academic performance in second language learning - Alfonso Abad Mancheño; Ana Cristina León Mejía; Roberto Sánchez Cabrero (Institute of Advanced Engineering and Science, 2022)
This article presents the results of a research study on the role that affective motivation plays in learning a second language (L2). There were 171 American university students of Spain, German, Italy, and Japan as a second language participated in the study. This was an ex post facto, cross-sectional, and correlational quantitative study that informs us of which is the type of motivation most beneficial for learners and considers variables such as age, gender, academic performance, and the intention to continue studying a second language. An online questionnaire based on the Dörnyei motivational model was administered. The results show that the variables ideal self and “projection of intended effort” of the learners are positively and significantly related to the academic performance of the students and to the intention of enrollment in future foreign language classes. At the opposite extreme, the deontic self or ought-to-self does not correlate significantly with any of the rest of the variables considered. Regarding the cross-sectional analysis of age and gender, no significant differences were found in gender. However, there was a negative and significant correlation between age and academic performance. Furthermore, there was positive and significant correlation between age and projected effort.